2023
DOI: 10.1111/cns.14071
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel disease burden predicts functional outcomes in patients with acute ischemic stroke using machine learning

Abstract: Aims: Our purpose is to assess the role of cerebral small vessel disease (SVD) in prediction models in patients with different subtypes of acute ischemic stroke (AIS). Methods:We enrolled 398 small-vessel occlusion (SVO) and 175 large artery atherosclerosis (LAA) AIS patients. Functional outcomes were assessed using the modified Rankin Scale (mRS) at 90 days. MRI was performed to assess white matter hyperintensity (WMH), perivascular space (PVS), lacune, and cerebral microbleed (CMB). Logistic regression (LR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…They found that among above mentioned markers, only myeloperoxidase levels were altered, and this element was considered an important feature in the detection and prediction of cSVD. Wang et al [ 104 ] assessed the prognostic ability of SVD imaging markers on acute ischemic stroke subtypes using machine learning and logistical regression methods and found that in lacunar stroke patients, models using SVD imaging markers could rapidly predict prognosis. Nevertheless, the mechanism by which SVD affects the prognosis of acute ischemic stroke patients is poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…They found that among above mentioned markers, only myeloperoxidase levels were altered, and this element was considered an important feature in the detection and prediction of cSVD. Wang et al [ 104 ] assessed the prognostic ability of SVD imaging markers on acute ischemic stroke subtypes using machine learning and logistical regression methods and found that in lacunar stroke patients, models using SVD imaging markers could rapidly predict prognosis. Nevertheless, the mechanism by which SVD affects the prognosis of acute ischemic stroke patients is poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, radiomics performed well in predicting RTLI as it can detect microstructural changes in the temporal lobe early ( 11 ), enhancing prediction accuracy, as seen in the meta-analysis for each subgroup above. ML methods are required to process high-dimensional mineable data like radiomics, and these methods have been shown to play a crucial part in predictive models based on radiomics and standard clinical characteristics, such as predicting rapidly deteriorating mild cognitive impairment in Alzheimer’s disease ( 13 ) and the prognosis of acute ischemic stroke ( 12 ). LR is the most often used ML approach for building models due to its ease of use and consistently good performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous models were constructed without radiomics due to the limitations of manual data processing in handling large volumes of complex data. An increasing number of promising studies have attempted to employ machine learning (ML) approaches to develop prediction models relying on radiomics ( 12 , 13 ). The biggest strength of this kind of model is the personalized prediction at the early stage of RTLI whereas the biggest weakness is the dependence on imaging data, which may lead to possible additional medical expenses.…”
Section: Introductionmentioning
confidence: 99%
“…Association between CSVD and stroke outcome has been studied extensively, but still inconclusive (7,(13)(14)(15). While its predictive value in early neurological deterioration has not been comprehensively investigated.…”
Section: Csvd and End In Isolated Pontine Infarctionmentioning
confidence: 99%